Dampak Urbanisasi Bagi Pembangunan Manusia 2010-2016 Studi Kasus: Jakarta, Surabaya Dan Medan - Iwan Prasodjo (Jurnal Ekonomi, 2018)
This article discusses the effect of urbanization on the Human Development Index during 2010-16. It shows that Jakarta has the highest population growth and Gross Domestic Regional Product. However, Surabaya has the highest Human Development Index. Even though,  Jakarta, with the highest  Gross Domestic Regional Product,  does not indicate the highest Human Development Index. On the other hand, Medan has the lowest Gross Domestic Regional Product.  Not only does Medan has the lowest  Gross Domestic Regional Product, but also it has the lowest Human Development Index.